Optimization of Capillary Zone Electrophoresis and Micellar Electrokinetic Capillary Chromatography - Ghowsi, Kiumars; Ghowsi, Hosein (Asian Journal of Chemistry, 2011)
Optimization of capillary zone electrophoresis based on an electrosmotic mobility of ions. A new optimum condition relating electrophoretic mobility of ions and electroosmotic mobility was obtained using new resolution equation proposed in previous work incorporating effective length. Optimization of micellar electrokinetic capillary chromatography was done on the new resolution equation proposed in previous work based on incorporating effective length. This optimization for micellar electrokinetic capillary chromatography was done for resolution and tR/Rs2 which tR is retention time and Rs is the resolution.